1985
DOI: 10.1159/000173039
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Endogenous Natriuretic and Digoxin-Like Immunoreacting Activities in Human Urine: Effects of Changes in Sodium Intake

Abstract: In the present study natriuretic activity and digoxin-like immunoreacting activity (DLIA) were determined in small molecular weight (MW) fractions of urine from healthy subjects during low (35 mmol/day) and high ( > 400 mmol/day) sodium intake by bioassay and by a radioimmunoassay for digoxin, respectively. After gel filtration of urine on a Sephadex®G-25 column the natriuretic activity appeared in the post-salt fraction SIV, whereas DLIA was present in small amounts in the salt fraction SIII and, with consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1
2

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
0
15
1
2
Order By: Relevance
“…In a recent study using NMR and mass spectrometry analyses [31] we reported, in contrast to previous reports [8, 24,40], that a pure digitalislike compound isolated from human urine was not a peptide. The chemical structure of the purified urine-derived digitalislike compound is presently under investigation.…”
contrasting
confidence: 86%
See 1 more Smart Citation
“…In a recent study using NMR and mass spectrometry analyses [31] we reported, in contrast to previous reports [8, 24,40], that a pure digitalislike compound isolated from human urine was not a peptide. The chemical structure of the purified urine-derived digitalislike compound is presently under investigation.…”
contrasting
confidence: 86%
“…antibodies [8,17,21,22,[24][25][26][27][30][31][32][33][34][35],86Rb uptake inhibition [15, [28][29][30]361 and inhibition of Na+ pump activity [16,18,301. Digitalis-like compound measurements, using some of these methods, have revealed an increased plasmatic activity in end-stage renal diseases [19,20,28,35,371, in Na'-dependent experimental hypertension [36, 381 and in some essential hypertensive patients [lo, 11,13,17,19,201.…”
mentioning
confidence: 99%
“…Klingmuller et al(1982) found digitalislike immunoreactivity in the urine of sodium loaded normal human subjects. However, recent studies Kramer et al, 1985) have shown a lack of correlation between the digoxin-like immunoreactivity and either sodium intake or total natriuretic activity by bioassay. The present results showing dissociation of digoxin-like immunoreactivity from Nat, K+-ATPase inhibitory activity in fractionated urine and a lack of increased digoxin-like immunoreactivity in crude urine extract during high sodium intake are in agreement with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since an endogenous Nat, K+-ATPase inhibitor is postulated to play a physiological role in the control of sodium balance and blood pressure, a number of laboratories have made concerted efforts to isolate and identify this substance (Haber and Haupert, 1987). However, there is disagreement concerning the chemical nature, whether peptides (Gruber et al, 1980;Kramer et al, 1985;Morgan et al, 1985), steroids (Cloix et al, 1985;Vasdev et al, 1985) or lipid compounds (Tamura et al, 1985;Kelly et al, 1986). The conflicting results may be due to various relevant and irrelevant substances.…”
mentioning
confidence: 99%
“…They therefore suggested that these compounds could be peptidic. Kramer et al 20 extracted natriuretic fractions with EDLC characteristics from the urine of salt-loaded normal subjects. Amino acid analysis revealed that both natriuretic factors directly purified and the natriuretic material bound to the digoxin antibody had four amino acids in similar ratios.…”
Section: Peptidesmentioning
confidence: 99%